The Analysis of Attractant Compound From Neoregelia spectabilis As Breeding Site of Aedes albopictus - Fita Fita (Jurnal Matematika dan Sains (JMS), 2023)
The control of the Aedes albopictus mosquito vector still relies on the use of insecticides. The use of insecticides if not appropriate can have a negative impact on the environment and non-target organisms. Neoregelia spectabilis is a plant from the Bromeliaceae family which is often used as a natural breeding site for Aedes albopictus. In addition to the morphological factors, it is suspected that there are interesting chemical compounds that make this species a breeding site for Aedes albopictus mosquitoes. This study aimed to analyze the content of chemical compounds that are attractants from the plant species Neoregelia spectabilis. The research method began with taking samples of young leaves, extracting them by maceration, concentrating with a rotary vacuum evaporator and testing the content of compounds using the GCMS Variant Sarurn 2000. The results of the GCMS analysis showed that the chemical compounds present in Neoregelia spectabilis are compounds from the groups of alcohols, alkanes, esters, and terpenes One of the attractant compounds found is a compound from the alkane group. The group of alkane compounds was found as much as 50.63%.